1987
DOI: 10.1016/0016-5085(87)90924-3
|View full text |Cite
|
Sign up to set email alerts
|

Different response to epidermal growth factor of hepatocytes in cultures isolated from male or female rat liver

Abstract: Deoxyribonucleic acid (DNA) synthesis in hepatocytes isolated from the livers of male and female rats has been compared in monolayer culture. Plating efficiency, DNA and protein content, viability, and morphologic appearance were the same in cultures prepared with hepatocytes isolated from male or female rats. Epidermal growth factor (EGF)-induced DNA synthesis was significantly higher in hepatocytes from male rats than in hepatocytes from female rats. This was the case whether hepatocytes were isolated from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

1988
1988
1997
1997

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…Hepatocytes were isolated by modification of the in situ two-step collagenase perfusion technique of Seglen [15], as previously described [16]. The purity of the preparation was more than 98%, as demonstrated by the staining for glucose-6-phosphat ase [16].…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocytes were isolated by modification of the in situ two-step collagenase perfusion technique of Seglen [15], as previously described [16]. The purity of the preparation was more than 98%, as demonstrated by the staining for glucose-6-phosphat ase [16].…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of cytosolic, nuclear, and plasma membrane fractions was as described previously (10,15). The methods for the estrogen receptor assay (10) and the EGF binding assay have been described previously (15).…”
Section: Binding Studiesmentioning
confidence: 99%
“…The methods for the estrogen receptor assay (10) and the EGF binding assay have been described previously (15).…”
Section: Binding Studiesmentioning
confidence: 99%
“…Efforts to identify and purify the active constituent in the cytosol of rat livers were hampered by the inability to settle on an appropriate assay. Fractions prepared by other investigators were reported to be mitogenic in tissue cultures of hepatocytes or hepatoma cells (12,13,15), whereas ours were inert in vitro throughout purification to the final fraction used for amino acid sequence analysis and cDNA cloning (9,10,26).…”
Section: Discussionmentioning
confidence: 68%
“…The method of purification of ALR from male Fisher weanling rats was as reported (9,10). The procedures involved the following successive steps: ethanol precipitation, ultrafiltration through an Amicon PM30 membrane, cation-exchange FPLC on a Mono Q column, and nondissociating PAGE.…”
mentioning
confidence: 99%